Implementation of Whistleblowing System in a Hierarchical Public Organization: Evidence from Indonesian Customs - Tasya Alya Salsabila; Anantawikrama Tungga Atmadja; Putu Sukma Kurniawan (Lembaga Riset Ilmiah, 2026)
Whistleblowing systems have become an essential governance mechanism for detecting and preventing misconduct in public sector organizations. However, their effectiveness is frequently constrained by hierarchical organizational structures and workplace culture, resulting in a gap between the formal availability of reporting mechanisms and their actual utilization. This study aims to examine the implementation of the whistleblowing system and identify the organizational barriers affecting its utilization within a hierarchical public organization. The study offers a novel contribution by explaining how hierarchical authority, informal communication practices, and organizational culture interact to shape employees’ reporting behavior, thereby extending existing whistleblowing research beyond individual reporting intention toward organizational implementation. A qualitative case study was conducted at the Ngurah Rai Customs and Excise Office (KPPBC Ngurah Rai), Indonesia. Data were collected through semi-structured interviews, observations, and document analysis and analyzed using thematic analysis. The findings reveal that although the whistleblowing system has been formally integrated into the organization's internal control framework, it functions primarily as a last-resort reporting mechanism rather than an early warning system. This limited utilization is driven by organizational barriers, including limited transparency in report follow-up, inadequate understanding of reporting procedures, low employee awareness, the absence of incentives for whistleblowers, concerns over workplace relationships, and hierarchical power dynamics that discourage formal reporting. The study demonstrates that the effectiveness of whistleblowing systems depends not only on the availability of reporting channels but also on organizational trust, transparency, leadership support, and a strong ethical culture that encourages speak-up behavior. The findings contribute theoretically by advancing the understanding of whistleblowing implementation in hierarchical public organizations and provide practical recommendations for strengthening reporting mechanisms and improving organizational integrity within government institutions.